Syntagmatic and Paradigmatic Approaches in Vocabulary Classification: A Comprehensive Overview ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
Vocabulary classification plays a crucial role in understanding and organizing language. One important point maybe about the lexical system, whose elements are characterized by their combinatorial and contrastive properties determining their several relationships. Two fundamental approaches, namely the syntagmatic and paradigmatic approaches, have been employed to categorize and analyze vocabulary. This article aims to delve into these approaches, exploring their definitions, differences, and significance in understanding the structure and function of language.